Auf dem Weg zur Normalität Konflikt und Verständigung in den deutsch-französischen Beziehungen der 1970er Jahre - Petter, Dirk (Pariser Historische Studien, 2014)
Despite the fortuitous leadership of Giscard and Schmidt, German-French relations during the 1970s experienced a series of major conflicts. There were a number of different governmental and societal forces that sought to resolve them. Dirk Petter examines this interplay of conflict and rapprochement and interprets the critical decade of the 1970s in the overall context of post-war relations between Germany and France.